Effect of soil amendments on damping-off disease of tomato. - Balofinos, Junnel B. (1998.)
Different soil amendments obtained commercially were tested for their ability supress damping-off disease of tomato. Compost, animal manure, inorganic fertilizer, and green manure were applied to autoclaved soil prior to addition of a pathogenic inoculum. The bilogical control of the damping-off disease was evaluated by monitoring disease incidence inevery plot of 50 seedlings for 25 days. Compost and animal manure significantly reduced disease incidence while green manure and inorganic fertilizer did not yield significant results as compared to the non-amended control soil. Percent emergence, dry matter content, and height were not all affected by the different treatments.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Soil amendments